The Impact of the Difficult Economic Situation on the Operation of Slovak Companies in the Shadow of War - POÓR, József; KOSÁR, Silvia TÓBIÁS; HUSZÁRIK, Erika Seres; ZSIGMOND, Tibor; SZABÓ-SZENTGRÓTI, Gábor; TÓTH, Zsuzsanna (Journal of Ecohumanism, 2024)
Purpose: The purpose of this study is to examine the organizational and human resource (HR) responses to the challenging economic conditions caused by the war and the COVID-19 pandemic. Given the limited evidence available on how organizations adapt to such crises, this research aims to develop a conceptual model and empirically investigate the influence of two specific factors: organizational size and direct economic ties with the Russian and Ukrainian markets. Methodology: This study employs a mixed-method approach, combining both theoretical and empirical research. A conceptual model was first developed to outline potential organizational reactions to crisis conditions. The empirical part of the study involved data collection from 128 organizations, including companies and institutions, in Slovakia. The analysis was conducted to test two hypotheses regarding how organizational size and economic connections with the Russian and Ukrainian markets affect organizational and HR responses in times of war. Findings: The findings of the study indicate that neither organizational size nor direct economic linkages with the Russian and Ukrainian markets significantly influenced the responses of the organizations studied to the economic difficulties caused by the war. This suggests that other factors may play a more critical role in shaping organizational and HR strategies in response to crises. Implications for theory and practice: For theory, this study contributes to the existing literature by challenging the assumption that organizational size and direct economic ties to conflict-affected markets are primary determinants of organizational responses to crisis. For practice, the findings suggest that managers and HR professionals need to consider a broader range of factors beyond size and market exposure when developing strategies to cope with economic disruptions caused by global crises. Originality and value: This research is original in its focus on the specific impacts of war and pandemic-induced economic conditions on organizations in Slovakia. The study provides valuable insights into how organizations navigate crises, expanding the understanding of crisis management and organizational adaptability. It adds value by highlighting the need for more comprehensive models that consider a wider array of factors influencing organizational behavior in times of global economic disruption.